The Effect of Land Degradation on Potato Production in Rubanda District: A Case Study of Muko Sub-County. - Niwaha, Richard (Kabale University, 2023)
The aim of the study was to establish the effect of land degradation on potato production in Muko Sub County. The study was guided by objectives which were; to determine the types of land degradation in Muko Sub County, to investigate the land degradation factors affecting potato production in Muko Sub County and to establish the measures to reduce land degradation and improve potato production in Rubanda District. The study adopted a descriptive research design and a sample of 171 respondents. Purposive and simple random sampling techniques were used in selecting respondents. Questionnaires and interview guide were used in data collection. Data was presented using frequency tables, pie-charts and graphs. Findings in revealed that 35.1% of the respondents reported that there was soil fertility decline in the study area, 29.2% of the respondents reported soil erosion, 14.6% of the respondents revealed that there was vegetation loss in Muko sub county, 11.7% of the respondents reported stone appearance while 9.4% revealed that there was waterlogging in Muko sub county. From the findings, 23.4% of the farmers ranked insufficient capital as the major constraints to potato farming, 20.5% and 17.5% of the farmers ranked high cost of farm inputs and pests and disease respectively, 11.7% reported inadequate storage. It was noted by 20.5% of the farmers that terracing improves land degradation and increases potato production. Agroforestry practices improves on soil conservation and improves on productivity of potato production was reported by 19.3% of the respondents. Controlled overgrazing reduces land degradation and increases productivity of land for potatoes as revealed by 16.4% of the respondents. More still, 14.6% of the farmers revealed that provision of information to potato farmers on improved potato technologies by extension workers reduce land degradation and improve potato production. The study found out that insufficient capital, high cost of farm inputs and pests and disease, inadequate storage, poor information network, insufficient extension agent and lack of access road were the challenges faced by farmers in potato production. It was recommended that extension agents should be well involved in disseminating information by using open field days, demonstration and control plots so as to encourage farmers in adopting better production practices. Government and other stakeholders need to also invest in extension service in sensitizing potato farmers in the study areas as this has the potential to increase farmer’s productivity and income.